Pain Behind the Silence - Nishonova Mohidil (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article explains how women can protect their violated rights and how women subjected to violence are protected by the state. It also demonstrates the principle of equality between women and men, emphasizing that both genders have equal rights and opportunities in all spheres of life. The events described in the article are based on real-life situations.